Analysis Of Food Diversification Policy In Overcoming The Food Crisis - Widiastuti, Ika; Himawan, Himawan (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2021)
The food crisis is a threat to all countries. Thinking must be changed from foodsecurity to food self-sufficiency. The policy in overcoming the food crisis is bydiversifying food. Food diversification is food diversification with balanced nutrition.Barriers to the development of local food are undeveloped products and people's thinking that rice is a staple food. The development of local food products is the provision of income for the food industry.